Face spoofing detection - Siew, Frans Yan Shen (Nanyang Technological University, 2022)
There has been a growing adoption of face recognition systems being used for biometric authentication. Therefore, it is crucial to ensure that facial recognition systems are safe from malicious impersonation attempts to gain access. Which could to theft of confidential information or valuables stored in applications these systems are typing to protect